The Minimum Alveolar Concentration of Sevoflurane for Respiratory Depression - V. V. Likhvantsev; E. M Kozlova; S. A. Fedorov; A. V Mironenko; D. D. Selivanov (Общая реаниматология)
Objective: to provide a rationale for a need to introduce the new constant — the minimum alveolar concentration for respiratory depression (MACrespiratory depression) and to determine its value. Subjects and methods. Forty-three patients aged 20— 45 years, who had normal weight and ASA physical status I—II, were examined. All the patients underwent induction of sevorane anesthesia without narcotic analgesics, nitrous oxide, and myorelaxants. A laryngeal mask was installed after MAClm was achieved. Sevorane concentrations were increased on a vaporizer, by changing Etanesth at a rate of 0.2 vol% per min until Etanesthresp;ratory depression was achieved. Results. A rationale was provided for a need to introduce the new inhalation anesthesia constant MACrespiratory depression that is, in accordance with the MAC conception, regarded as the inhalation anesthetic concentration that necessitates assisted ventilation in 50% of the patients. MACrespiratory depression was 1.8 MAC. This is essentially more than both MAC and 1.3 MAC, the anesthetic concentration at which any operation can be performed in 90% of patients. At the same time, the derived value of 3.7 vol% is somewhat below MACbarr (4.07 vol%), which means that anesthesia with sevorane only under spontaneous respiration will be inadequate in few patients or its performance will be associated with the risk of hypoxia. Conclusion. The authors’ successively developed concept of anesthesia with preserved spontaneous respiration necessitates the introduction of the new inhalation anesthesia constant MACrespiratory depression. Its value is 3.7% vol% for sevoflurane. Key words: induction of anesthesia, minimum alveolar concentration, spontaneous respiration, inhalation anesthesia.